Pemanfaatan Media Sebagai Saluran Untuk Memperoleh Informasi Tentang Investasi - Citra Pratiwi; Susi Yunarti; Arsiyati Arsiyati (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The rise of illegal investment cases that have occurred has become quite an interesting study in the midstof the many information media that can be accessed by the general public. This study aims to find outhow the use of media among millennials to obtain information about investment so as not to fall intoillegal investments. The research questions posed in this study are 1) regarding the understanding ofinvestment millennials? and 2) How is the use of media to get information about investment? The theoryused in this research is perception theory, and attribution theory. The paradigm of this research isconstructivist, using phenomenological method. Techniques for collecting data through the interviewmethod. The results showed that all informants already had the awareness to invest with several motivesincluding as a reserve fund to increase business capital, when there was a need, for education and forpreparation for old age. Based on this research, it was also found that investment literacy is still verymuch needed for millennials so that they understand more about the rules regarding investment so thatthey feel safe in investing.